Tailoring Robust 2D Nanochannels by Radical Polymerization for Efficient Molecular Sieving - Yue You; Yuxi Ma; Xianghui Zeng; Yichao Wang; Juan Du; Yijun Qian; Guoliang Yang; Yuyu Su; Weiwei Lei; Shuaifei Zhao; Yan Qing; Yiqiang Wu; et al. (Advanced Science)
Abstract Two‐dimensional (2D) nanochannels have demonstrated outstanding performance for sieving specific molecules or ions, owing to their uniform molecular channel sizes and interlayer physical/chemical properties. However, controllably tuning nanochannel spaces with specific sizes and simultaneously achieving high mechanical strength remain the main challenges. In this work, the inter‐sheet gallery d‐spacing of graphene oxide (GO) membrane is successfully tailored with high mechanical strength via a general radical‐induced polymerization strategy. The introduced amide groups from N‐Vinylformamide significantly reinforce the 2D nanochannels within the freestanding membranes, resulting in an ultrahigh tensile strength of up to 105 MPa. The d‐spacing of the membrane is controllably tuned within a range of 0.799–1.410 nm, resulting in a variable water permeance of up to 218 L m−2 h−1 bar−1 (1304% higher than that of the pristine GO membranes). In particular, the tailored membranes demonstrate excellent water permeance stability (140 L m−2 h−1 bar−1) in a 200‐h long‐term operation and high selectivity of solutes under harsh conditions, including a wide range of pH from 4.0 to 10.0, up to a loading pressure of 12 bar and an external temperature of 40 °C. This approach comprehensively achieves a balance between sieving performance and mechanical strength, satisfying the requirements for the next‐generation molecular sieving membranes.